AB1270 EVALUATIONS OF ANTIRHEUMATIC DRUGS AT PRECONCEPTIONAL, PREGNANCY AND POSTPARTUM PERIODS OF RA PATIENTS' IN A UNIVERSITY HOSPITAL; PRELIMINARY RESULTS. (June 2019) - Duman, Nesrin Caglayan; Karaalp, Atila; Inanc, Nevsun
Abstract : Background: Rheumatoid arthritis (RA) spontaneously improves during pregnancy and disease activity decreases in approximately two-thirds of pregnant but this decrease does not last long and postpartum exacerbation can be seen 1 .Conversely discontinuation of antirheumatic drug (ARD) during pregnancy may be a risk factor for exacerbation of RA 2 . In case of preconceptional, pregnancy and postpartum (P&P&P) situations during RA treatment, current options are discontinuation of inappropriate medications and switching to appropriate ones. With the latest BSR and EULAR guidelines on prescribing drugs in P&P&P, treatment options expanded with some of the biologic drugs 3, 4 . Objectives: The aim of this study is to analyse alterations of ARD use (discontinuation, increasing or switching) at P&P&P periods of RA patients' retrospectively between 2002-2018. Methods: In our records there are 25 cases of 19 female RA patients who having at least one pregnancy experienced out of 140 RA patients. The data were collected by telephone calls and patient file. Female patients that had no pregnancies after the RA diagnosis were not included. Preconception period was defined as 1 year before estimated last menstrual date. Postpartum period was defined as 1 year after infants' birth. Results: RA patients participating in our study of 140 female (age median 55 (26-87)), 121 of them (86%) did not give birth after the RA diagnosis. 19 of them (age median 39 (26-61)) had been pregnant after the RA diagnosis (%14) and 14 of them gave birth 1, 4 of them gave birth to 2, one of them gave birth to 3. Twelve out of 140 (9%) patients had postnatal diagnosis. Each of the pregnancies counted as one case so some female patients represented in our data more than ones. While 22 of cases used the ARD before pregnancy (88%), it decreased 18 of cases (72%) after giving birth. Drug use rate (n=12, 48%) was most lowest particularly 3. trimester and first 3 months after birth (Figure 1 ). While there was a change such as discontinuation, increasing or switching in the treatment of 15 patients (60%) compared to before and after pregnancy and 6 of them (24%) continued to increase treatment (added drug to preconception treatment). More than half of the patients used steroids and nonsteroidal antiinflammatory drug in all periods (Figure 2 ). Conclusion: In conclusion the present study suggests that RA patients and doctors avoid the use of ARDs other than steroids and NSAIDs in P&P&P periods. The fact that 60% of the patients undergoing postpartum drug change were showed that pregnancy affected the RA treatment regimen. The need for steroid and NSAID in a high proportion of patients during P&P&P periods indicates the continuation of RA disease activity and the necessity of strong RA treatments during all these periods. References: [1] Hazes JM, et al. Rheumatoid arthritis and pregnancy: evolution of disease activity and pathophysiological considerations for drug use. Rheumatology (Oxford). 2011 Nov;50(11):1955-68. [2] van den Brandt S, et al. Risk factors for flare and treatment of disease flares during pregnancy in rheumatoid arthritis and axial spondyloarthritis patients. Arthritis Res Ther. 2017 Mar 20;19(1):64. [3] Flint J, et al. BSR and BHPR guideline on prescribing drugs in pregnancy and breastfeeding-Part I: standard and biologic disease modifying anti-rheumatic drugs and corticosteroids. Rheumatology (Oxford). 2016 Sep;55(9):1693-7. [4] Götestam Skorpen C, et al. The EULAR points to consider for use of antirheumatic drugs before pregnancy, and during pregnancy and lactation. Ann Rheum Dis. 2016 May;75(5):795-810. Disclosure of Interests: None declared